Composition Of The Types Of Stingrays Landed By Fishermen In The Mouth Of The River, Batu Kumbang Beach, In Island Baru Village, Ipuh District, Mukomuko Regency - Irfan Saleh (Justek : Jurnal Sains dan Teknologi, 2022)
Abstract: This study aims to determine the composition of species and the distribution of length and weight distribution of stingray caught by fishermen who landed at the mouth of the Batu Kumbang Beach River, Pulau Baru Village, Ipuh District, Mukomuko Regency. The method used is a survey method, followed by collection of length and weight measurement data from various species of stingray were found. From the results of the study found 4 families of 10 species of stingrays as many as 52 fish including Himantura gerrardi, Taeniura lymma, Rhinoptera jayakari, Dasyatis kuhlii, Himantura uarnak, Himantura jenkinsii, Rhinoptera javanica, Aetobatus ocellatus, Himantura pastinacoides and Rhynchobatus australiae. There were 4 dominant species of stingray caught, namely Rhinoptera jayakari (23.08%), Himantura gerrardi (21.15%), Himantura jenkinsii (11.54%) and Aetobatus ocellatus (9.62%). As for the distribution of length and weight distribution of the dominant stingray species, the  stingray caught was  dominated by small size  or still in its infancy (saplings). There are 3 fishing gear used, namely gill nets, longline fishing rods and shrimp trawls.  The  stingray  caught  is  aby- catch. All types of rays caught are included in the IUCN list.Abstrak: Penelitian ini bertujuan untuk mengetahui komposisi jenis dan sebaran panjang dan sebaran berat ikan pari yang tertangkap oleh nelayan yang mendarat di Muara Sungai Pantai Batu Kumbang Desa Pulau Baru Kecamatan Ipuh Kabupaten Mukomuko. Metode yang digunakan adalah metode survei, dilanjutkan dengan pengumpulan data pengukuran panjang dan berat dari berbagai spesies ikan pari yang ditemukan. Dari hasil penelitian ditemukan 4 family dari 10 jenis ikan pari sebanyak 52 ekor diantaranya Himantura gerrardi, Taeniura lymma, Rhinoptera jayakari, Dasyatis kuhlii, Himantura uarnak, Himantura jenkinsii, Rhinoptera javanica, Aetobatus ocellatus, Himantura pastinacoides dan Rhynchobatus australiae. Ikan pari yang dominan tertangkap ada 4 jenis yaitu pari jenis Rhinoptera jayakari (23,08%), Himantura gerrardi (21,15%), Himantura jenkinsii (11,54%) dan Aetobatus ocellatus (9,62%). Adapun sebaran panjang dan sebaran berat dari jenis pari yang dominan bahwa ikan pari yang tertangkap didominasi berukuran kecil atau masih dalam masa pertumbuhan (anakan). Terdapat 3 alat tangkap yang digunakan yaitu jaring insang, pancing rawai dan pukat udang. Ikan pari yang tertangkap merupakan hasil tangkapan sampingan (by catch). Semua jenis pari yang tertangkap termasuk kedalam daftar list IUCN.